First Author Determinants: An Empirical Analysis - Mirjam van Praag; Bernard M.S. van Praag (Tinbergen Institute, 2006)
Alphabetic name ordering on multi-authored academic papers_new, which is the convention in theeconomics discipline and various other disciplines, is to the advantage of people whose lastname initials are placed early in the alphabet. As it turns out, Professor A, who has been afirst author more often than Professor Z, will have published more articles and experienced afaster growth rate over the course of her career as a result of reputation and visibility.Moreover, authors know that name ordering matters and indeed take ordering seriously:Several characteristics of an author group composition determine the decision to deviate fromthe default alphabetic name order to a significant extent.
Keywords: A11; A14; J32; J44; 330; performance measurement; incentives; economists; name ordering; Bibliometrie; Ökonomen; Ranking-Verfahren